ЕРТЕК ТИП СЮЖЕТЛИ ҲӘМ ТАРИЙХЫЙ-ҚАҲАРМАНЛЫҚ ДӘСТАНЛАРДА ДАРАЛЫҚ ДӨРЕТИЎШИЛИК ДӘСТҮРЛЕРИ КӨРИНИСЛЕРИ - Кеңесбаева, Ш.К. (SCIENCE and SOCIETY, 2022)
The article analyzes the fact that fairy-tale epics such as "Shahriyor", "Shiyryn Sheker", "Qanshayym", "Munlyq - Zarlyq" are a new aesthetic system, not in terms of genre, but in terms of creativity. The article also examines the epic "Amanbay batyr" from this point of view.